Poverty is a public bad: Panel evidence from subjective well-being data - Heinz Welsch; Philipp Biermann (University of Oldenburg, Department of Economics, 2016)
Previous research has found that subjective well-being (SWB) is lower for individuals classified as being in poverty. Using panel data for 39,239 individuals living in Germany from 2005-2013, we show that people's SWB is negatively correlated with the state-level poverty ratio while controlling for individual poverty status and poverty intensity. The negative relationship between aggregate poverty and SWB is more salient in the upper segments of the income distribution and is robust to controlling for the rate of unemployment and per capita GDP. The character of poverty as a public bad suggests that poverty alleviation is a matter not only of equity, but of efficiency.
Keywords: I31; I32; D60; 330; poverty; poverty ratio; subjective well-being; public bad; life satisfaction